Time-space of possibilities: translocal geographies of Latvians in Guernsey - Lulle, Aija (Latvijas Universitāte, 2014)
Promocijas darba autore radoši izmanto laika ģeogrāfijas perspektīvu, izveidojot translokālu modeli, ar kura palīdzību tiek analizēti migrācijas veidi no vienas puses un klātbūtnes/prombūtnes pieredze no otras puses. Pētījuma pamatu veido kvalitatīvās metodes: intervijas, novērojumi un ģeogrāfiskās mobilitātes līdzdalīgais novērojums no 2010. gada līdz 2012. gadam. Šis ir pirmais detalizētais pētījums vienā no Lielbritānijas salām – Gērnsijā, kas pēdējo 20 gadu laikā piesaistījusi migrantus no Latvijas. Ģeogrāfiski norobežotas vietas mērogs kopsaistē ar Eiropas Savienības pilsoņu brīvas pārvietošanās iespējām veido īpašus ierobežojumus un iespējas laiktelpā, kurā īslaicīga migrācija pārtop cirkulārā migrācijā, darbavietu un ģimenes stāvokļa maiņa veido hierarhiskas pozīcijas un ierobežojumi uzturēties salā ietekmē atgriešanās vizīšu biežumu, ilgumu, saikni ar atpakaļmigrāciju, atkārtotu emigrāciju un migrācijas virzienu maiņu uz citām vietām Eiropā. No teorijas viedokļa pētījums ir nozīmīgs laika ģeogrāfijas perspektīvas pilnveidē, padziļinot tās lietojumu translokālas mobilitātes un subjektīvās pieredzes izpētē. Pētījums arī sniedz ieguldījumu, analizējot ģeogrāfiski norobežotu teritoriju Eiropā, un paplašina īslaicīgu ģeogrāfiskās mobilitātes veidu līdzšinējos skaidrojumus.

This thesis proposes a time-geographic perspective in order to investigate the circular migration pattern of Latvian labour migrants in the Channel Island of Guernsey. The research makes two main contributions to geographical scholarship on migration. The first is theoretical: the mobilisation of a whole series of concepts such as trajectory and project, the choreographies of time-space corporeal movements, the notion of constraints to mobility, and the time-space of possibilities, all of which derive from or are outgrowths of Hägerstrand’s time-geography. The second contribution is place-specific, and this is the documentation of a very specific migration system, that from Latvia to Guernsey, which has never been analysed before, and which exhibits both singular features and certain general characteristics which are potentially applicable to other circular labour migration systems which evolve under conditions of free movement yet are still subject to certain constraints. Latvians are possibly the largest migrant group in Guernsey and since the 1990s have been recruited to work mainly in horticulture, hotels, and other sectors such as cleaning and care work. The insular microcosm and geographical boundedness of Guernsey, as well as the relatively small scale of Latvia, create an effective spatial laboratory of the in-depth study of the possibilities and constraints in time-space of Latvians to attain ‘better-life’. The research is based on qualitative methods: in-depth interviews, observation, and participation in episodes of actual geographical mobility. Fieldwork was undertaken in five phases during 2010–2012. As well as regimes of short-term and circular migration, initially constrained by limited housing and work-permit rights but latterly evolving into longer-term settlement for some Latvians, the thesis studies other contingent or ‘enfolded’ mobilities, such as visits back and forth, and prospects for a definitive return to Latvia. Theoretically, the research contributes the following fresh insights into migration research. First, it is a pioneering application of the framework of time-geography into international migration and its associated mobilities. Second, the time-geographic approach is articulated through the spatial lens of emplaced translocal mobilities and subjectivities. And third, it combines the time-geography optic with the more phenomenological perspectives of everyday experiences, lifeworlds, mobile genres de vie, and wellbeing.
Iespēju laiktelpa: translokāla ģeogrāfiskā mobilitāte no Latvijas Gērnsijā
Keywords: Ģeogrāfija; laika ģeogrāfija; mobilitāte; translokālā ģeogrāfija (Latvija, Gērnsija); Human geography; time-geography; mobility; translocal geography (Latvia, Guernsey)